Performance or Participation...Pluralism or Hegemony? Images of Disability and Gender in Sports 'n Spokes Magazine - Marie Hardin; Brent Hardin (Disability Studies Quarterly, 2005)
The purpose of this study is to examine the photographic images of Sports 'n Spokes magazine to explore the relationship between sport, disability and gender. Photographs in 24 issues of Sports 'n Spokes were collected and examined via content analysis. A recording instrument was developed by the researchers to code 2,141 editorial images. The instrument was adapted for use with images of disability and the categorical variables were: (a) gender of the subject; (b) disability; (c) type of sport participation; (d) competition in sport; (e) motion; and (f) camera angle. The findings indicate that men dominated photographic coverage in Sports 'n Spokes and were more likely to be depicted in dominant photos and as sports competitors than women. Women were more often depicted as non-sporting, and women were depicted less often as competitors. However, the magazine includes women to a much greater degree than mainstream (able-bodied) sports magazines. The magazine also reflects pleasure/participation (versus power/performance) as a valid sporting value.
Keywords: disability sports; Sports & #x27; n Spokes magazine; gender and sports